Taboo Language in Political Discussions in X (Twitter) - Su-Hie TING; Amanda Christy Hanis; Humaira Raslie (Universitas Nahdlatul Wathan Mataram, 2026)
The study examined the use of taboo language in political discourse on X (Twitter). The objectives of the study are to: (1) identify the Malay and English taboo words used in political discourse on Twitter, and (2) analyze the function of using Malay and English in political discourse on X. The descriptive study involved the collection of posts from X using the search words “politics” from 1 June 2022 to 31 August 2022 and with geotagging for “Malaysia”. A total of 126 tweets containing 202 posts with taboo words were identified. The analysis showed that the most common type of taboo words is insult and slur (59), followed by cursing (50) and epithets (49). There were less words on obscenity (14), vulgarity (13), slang (9), and scatology (8). No taboo words related to profanity and blasphemy were found. For the function of taboo words, the main function is discrediting other people or ideas (108). The X user used taboo words for other functions less frequently, namely, catharsis (46), strong interpersonal identification (39), attention-getting (7), and provoking of violent confrontation (2). A bigger range of taboo words in English was found for vulgarity and scatology but more taboo words in Malay were found for insult and slur, curse words, epithets, obscenity, and slang. The findings indicate respect for religious and ethnic sensitivities through the absence of blasphemy and profanities.